Otherness, Resistance, Blending and Hybridity Literary Representations of Immigrants - Gairaud Ruiz, Hilda (2021)
This article is part of the research project Pry01-1809-2020- “Literary Representations from the Border: The American Dream, Immigration, Power and Hyphenated Identities.” This research continues to explore the construction of subjectivities from immigrant populations represented in literary texts in order to compare their existential conditions either as part of the Otherness or as hybrid subjects traveling to or living in the U.S. It also introduces the discussion of the phenomenon of massive immigration from Latin-American countries, their notion of the American Dream, their motivations for leaving their countries of origin, migrating and their possibilities of attaining personal achievement for further discussion. This document compares the representation of subjectivity in Sandra Cisneros´ The House on Mango Street and Cristina Garcia´s Dreaming in Cuba to differentiate their constitution as marginal or privileged characters, to examine their possibilities